2020
DOI: 10.1093/ehjci/ehaa946.2137
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lambda and kappa light-chain cardiac amyloidosis in Polish patients diagnosed in cardiology department

Abstract: Background Lambda (λ) and kappa (κ) types of light-chain amyloidosis (AL amyloidosis) are believed to have a similar prognosis. Data on the comparison of these two types of cardiac amyloidosis is scanty. Objectives The aim of the study was to investigate wether lambda light-chain cardiac amyloidosis indicates worse prognosis than the kappa variety. Methods Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, recent study showed that prognosis in patients with kappa type AL cardiac amyloidosis was better than that in patients with lambda type AL cardiac amyloidosis. 3 In spite of the poor prognosis for patients with AL amyloidosis, HF presenting with symptomatic HF, chemotherapy and/or auto-PBSCT is associated with improved outcomes for eligible patients. 1 , 4–7 Therefore, the early detection of cardiac involvement of AL amyloidosis followed by specific treatment is essential for a favourable prognosis, but such early detection can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent study showed that prognosis in patients with kappa type AL cardiac amyloidosis was better than that in patients with lambda type AL cardiac amyloidosis. 3 In spite of the poor prognosis for patients with AL amyloidosis, HF presenting with symptomatic HF, chemotherapy and/or auto-PBSCT is associated with improved outcomes for eligible patients. 1 , 4–7 Therefore, the early detection of cardiac involvement of AL amyloidosis followed by specific treatment is essential for a favourable prognosis, but such early detection can be challenging.…”
Section: Discussionmentioning
confidence: 99%